Geophysical investigation and hydrocarbon potential of Cankiri-Corum Basin, Turkey - Aslan, Yasemin; Buyuksarac, Aydin; Erik, Nazan Yalcin; Aydemir, Attila; Ates, Abdullah (Elsevier Science Bv, 2013)
The Cankiri-Corum Basin is one of the larger, onshore sedimentary basins in central Turkey. In this paper, the integration of geophysical data and geological findings in the Cankiri-Corum Basin was performed and they both present a complex basin structure. In the frame of geophysical study, two-dimensional (20) models were constructed using gravity and magnetic anomalies. Seismic sections were interpreted and correlated with the 2D models using the borehole data as control. Basement depth, basin geometry and sources for magnetic anomalies along the 20 model profiles were determined in integration of seismic, gravity, aeromagnetic and borehole data. Seismic section CC-L-1 is correlated with the Topuzsaray-1 well. Tuffs and volcanic units penetrated in this well might be correlated across a reverse fault close to the borehole. Seismic sections, CC-L-2 and CC-L-3, are consistent with the gravity models at the deeper parts of the sections. On the other hand, there are inconsistencies in the shallow sections with the gravity models due to unexpected velocity variations in both the horizontal and vertical directions. The average depth of basement was found to be about 5 km by means of gravity modelling, which was correlated with the seismic sections. Magnetic anomalies are represented by intense values in the NW portion of the study area, but they indicate very low intensities in the middle of the map. A reverse magnetised body to the north of the study area was modelled in 2D along a profile and it was interpreted that this body might be an ophiolitic remnant. Polarities of many anomalies to the south and northeast of the region indicate remanent magnetisation. Alignment of the polarities extends in the northwest direction, indicating that the region rotated in the anticlockwise direction. Because there is around a 5 km sedimentary basin fill in the study area, it may exhibit hydrocarbon potential and the Yesilcat oil seep evidences this potential. Surface samples were collected to examine source rock potential and to correlate with the Yesilcat seep by analysing the organic geochemical properties. In this study, 72 samples were collected from different formations and it was found that the Yoncali Formation displays better source rock potential than the other formations studied. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cankiri-Corum Basin; Yesilcat seep; Topuzsaray; Sagpazari; two-dimensional modelling